2016
DOI: 10.1080/03007995.2016.1211997
|View full text |Cite
|
Sign up to set email alerts
|

High rate of non-treatment among osteoporotic women enrolled in a US Medicare plan

Abstract: Objective: To estimate the rate of non-treatment among elderly women with osteoporosis (OP) and to examine the association between patient characteristics and receiving treatment. Research design and methods: This cross-sectional, retrospective, observational study utilized patient information and claims from the Humana database to identify Medicare covered women aged 65 years old and continuously enrolled with evidence of either an OP diagnosis or an OP-related fracture during 2007-2011. The main outcome was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Previously performed studies in Europe and in the US have been based on register data for prevalence of osteoporosis and osteoporosis medication [ 10 , 11 , 31 ], and were therefore not able to fully take all relevant clinical risk factors into account. Being able to take most relevant clinical risk factors into account, we found in the present study that the treatment gap, according to NOF guidelines, in our older Swedish women was similar or somewhat lower than what was previously reported in older women in the US [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously performed studies in Europe and in the US have been based on register data for prevalence of osteoporosis and osteoporosis medication [ 10 , 11 , 31 ], and were therefore not able to fully take all relevant clinical risk factors into account. Being able to take most relevant clinical risk factors into account, we found in the present study that the treatment gap, according to NOF guidelines, in our older Swedish women was similar or somewhat lower than what was previously reported in older women in the US [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relevant criteria include the presence of osteoporosis at one or more densitometric site, prior fracture (particularly spine, hip, or multiple fractures), and high fracture probabilities. Irrespective of the criteria used, the uptake of bone-specific treatment is low [ 10 , 11 ]. A large Danish register study found that only a small fraction of the expected number of women with osteoporosis were diagnosed and that very few women with fractures received osteoporosis medication after age 50 years [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These criticisms have raised a hot debate[ 26 31 ], and most of the cited arguments have been countered on the basis of the existing literature, without reaching a definitive clarification of the question.…”
Section: Introductionmentioning
confidence: 99%
“…Suboptimal treatment is an issue even among women with a history of osteoporotic fracture, whose risk is particularly elevated for another fracture. As few as one of every four Medicare patients in the USA received treatment after fracture [7,8].…”
Section: Introductionmentioning
confidence: 99%